Differences in pain, disability, and psychological function in low back pain patients with and without anxiety - Jiang, Ying; Wang, Yizu; Wang, Rui; Zhang, Xiaogang; Wang, Xueqiang (Frontiers in Physiology, 2022)
Objectives: Non-specific low back pain affects people of all ages and is a leading contributor to disease burden worldwide. Chronic low back pain (LBP) reduces working hours, increases comorbidities, and increases rehabilitation needs. The aim of this study was to evaluate whether there were differences in pain, dysfunction, and psychological factors between two groups. The supplementary demonstrated the relationship between these influencing factors and anxiety. Methods: A cross-sectional study was designed to analyze the differences in pain, disability, and psychological function in non-specific LBP patients with and without anxiety. In total, 60 subjects were divided into two groups based on self-rated anxiety scores: 30 patients with SAS score ≥50 were in the low back pain with anxiety group, and 30 for the LBP without anxiety group with SAS score <50. The pain intensity was assessed using the Visual Analog Scale; psychological function, using the Pain Anxiety Symptoms Scale, the Tampa Scale for Kinesiophobia, and the Fear Avoidance Beliefs Questionnaire; functional disability, using the Oswestry Disability Index and the Roland–Morris Disability Questionnaire; quality of life using 36-Item Short-Form Health Survey questionnaire; and the quality of sleep using Pittsburgh Sleep Quality Index, and the relationships between variables and anxiety scores were estimated using Spearman correlation analysis. Results: A total of 60 participants were enrolled after self-rated anxiety was assessed and the full investigation was finished. The analyses showed significant differences of pain intensity (p = 0.034, disability (ODI, p = 0.007; RMDQ, p = 0.012) and psychological function (TSK, p = 0.000; PASS, p = 0.009; FABQ, p = 0.000; SF-36, p = 0.000; and PSQI, p = 0.000) between the two groups. Spearman correlation analysis showed that the anxiety score had significant positive correlations with functional disability (ODI, p = 0.004 and 95% CI = 0.112–0.573; RMDQ, p = 0.003, 95% CI = 0.135–0.586) and psychological function (TSK, p = 0.001, 95% CI = 0.174–0.612), excellent positive correlation with quality of sleep (PASS, p = 0.025, 95% CI = 0.031–0.512), and strongly negative correlations with the quality of life (SF-36, p = 0.000, 95% CI = 0.761–0.433). Conclusion: We recognized that anxiety in low back pain patients was mainly due to interaction with the intensity of pain, disability level, and a mass of psychological function. The future research direction could be to alleviate the anxiety on the comprehensive efficacy of patients with low back pain.